34‐2: PI‐Less IPS/FFS Liquid Crystal Displays Utilizing Reactive LC with Diphenylacetylene Moiety. Issue 1 (29th May 2019) - He, Rui; Ye, Yang; Oh, Eunche; Lee, Honggwon; Kang, Shin-Woong; Lee, Seung Hee; Lee, Myong-Hoon
Abstract : We proposed a fabrication method to achieve uniaxially homogeneous alignment of LC molecules by irradiating polarized UV light to a mixture of new reactive mesogen having diphenylacetylene moiety and host LC above clearing temperature without using any conventional polyimide alignment layer in a sandwiched cell. The IPS/FFS cell fabricated by the proposed technology exhibited excellent dark state, electro‐optical characteristics and robust reliability, which could contribute to the low‐cost and high‐performance LCDs.